New insights on the origin for rapakivi granites: U-Pb and Lu-Hf in zircon from Alto Candeias Intrusive Suite, Amazonian Craton, Brazil - Queiroz, Luiza Almeida Villar de (2024)
The Southwestern Amazonian Craton, in Rondônia state, Brazil, comprises multiple orogens with ages ranging from 1.8 to 1.0 Ga, where successive magmatic, metamorphic, and deformational processes reworked ancient rocks and produced new complexes and juvenile continental crust. Identification of the geochronological and petrographic characteristics of granitoids and terranes generated during such events is crucial for the recognition and distinction of their magma sources. A total of 64 samples collected from the Alto Candeias Intrusive Suite outcrops in Rondônia state recognized four different groups: (1) Monte Negro unit (rapakivi granites), (2) Buriti unit (equigranular to porphyritic granodiorites), (3) Campo Novo unit (medium to coarse-grained charnockites), and (4) Jacilândia unit (fine-grained granites). U-Pb geochronological data were obtained for each unit, with the following ages: 1350 ± 5 Ma (Monte Negro unit), 1350 ± 2 Ma (Buriti unit), 1349 ± 3 Ma (Campo Novo unit), 1348 ± 3 Ma, and 1349 ± 1 Ma (Jacilândia unit). The ages of the four granitic units are the same within error. Lu-Hf isotopic results presented in this study indicate that the Alto Candeias Intrusive Suite has the mantle as the magmatic source and that the continental crust coeval to the subduction process. This process led to the formation of I-type granitoids generated in the SW margin of the Amazonian Craton around 1350 Ma during San Ignacio orogeny.